Seasonal variations in somereproductive parameters of Dorper Rams in Hungary - Budai, Csilla; Oláh, János; Egerszegi, István; Jávor, András; Kovacs, András (Acta Agraria Debreceniensis, 2013)
The purpose of the present study was to test the hypothesis that season has an affect on semen quality and scrotal circumference of Dorper rams. The experiment was carried out with six Dorper rams aged between 15 and 18 month. Semen samples were collected with artificial vagina and volume, concentration (x 109/ml), total sperm number/ejaculate (x 109), mass motility (0–5), progressive motility (%), scrotal circumference (cm) was observed. Significant differences (P<0.05) were observed in concentration, total sperm number/ejaculate, scrotal circumference in different seasons. Volume was the highest in autumn (1.4±0.5 ml) and the lowest in the spring (1.3±0.4 ml). Concentration of semen was lower in spring (2.6±1.5 x 109) and summer (3.3±1.5 x 109) as compared to fall (4.1±1.1 x 109) (P<0.05). Regarding total sperm number/ejaculate (x 109), scrotal circumference (cm) all the seasons differed significantly (P<0.05), although the season had no effect on mass motility and progressive individual motility (P<0.05). In conclusion the present study showed that semen quality parameters and scrotal circumference of Dorper rams were better in autumn than in the other sea- sons.